Thymidine kinase 1 related to Prolif-like T cells promoted GBM through regulation of cell cycle and EMT signals: a comprehensive research based on multi-omics analysis and experimental validation - Deng, Wentao; Chang, Xiaoting; Shang, Wei (Frontiers in Immunology, 2025)
BackgroundGlioblastoma (GBM) is a common high-grade glioma characterized by a significantly immuno-suppressed immune microenvironment. Prolif-like T cells are a subset of T cells whose expression of related markers can influence the tumor microenvironment.MethodsThis study used scRNA-seq and stRNA-seq to identify markers associated with Prolif-like T cells in the GBM tumor microenvironment. Survival analysis and consistency clustering were then employed to identify GBM subtypes associated with Prolif-like T cells, followed by an analysis of differences between subtypes. This study constructed survival models and scRNA-seq to screen for important genes associated with Prolif-like T cells in GBM and further investigated the role of TK1 in the cell cycle and EMT processes of GBM.ResultsUsing scRNA-seq from 149002 GBM cells, our study identified 593 Prolif-like T cell-related markers. The results of stRNA-seq revealed the close association of Prolif-like T cell with cell cycle and EMT signals. In addition, 82 genes were found to influence GBM prognosis. Based on the expression of the 82 genes, two Prolif-like T cell-related GBM subtypes (C1 and C2) were constructed, with C1 exhibiting stronger proliferative activity. Survival models and scRNA-seq identified TK1 as a key gene associated with Prolif-like T cells in GBM. Further studies revealed that TK1 promotes GBM progression by influencing cell cycle and EMT processes, and targeting TK1 inhibition suppresses GBM proliferation and migration.ConclusionsTK1, as a Prolif-like T cell-associated marker, promotes GBM progression and can serve as a potential therapeutic target for GBM.